Effect of substrate topography on the regulation of human corneal stromal cells. - Ahearne, Mark (My University, 2020)
Optimal functionality of native corneal stroma depends on a well-ordered arrangement of extracellular matrix (ECM). To develop an in vitro corneal model, replication of the corneal in vivo microenvironment is needed. In this study, the impact of topographic cues on keratocyte phenotype is reported. Photolithography and polymer moulding were used to fabricate microgrooves on polydimethylsiloxane (PDMS) 2-2.5 μm deep and 5 μm, 10 μm, or 20 μm in width. Microgrooves constrained the cells body, compressed nuclei and led to cytoskeletal reorganization. It also influenced the concentration of actin filaments, condensation of chromatin and cell proliferation. Cells became more spread and actin filament concentration decreased as the microgroove width increased. Relationships were also demonstrated between microgroove width and cellular processes such as adhesion, migration and gene expression. Immunocytochemistry and gene expression (RT-PCR) analysis showed that microgroove width upregulated keratocyte specific genes. A microgroove with 5 μm width led to a pronounced alignment of cells along the edges of the microchannels and better supported cell polarization and migration compared with other microgroove widths or planar substrates. These findings provide important fundamental knowledge that could serve as a basis for better-controlled tissue growth and cell-engineering applications for corneal stroma regeneration through topographical patterns.
PUBLISHED
Keywords: Biomaterial; Cell adhesion; Cell migration; Keratocytes; Microgrooves; Morphology